"We're All the Same Here"—Investigating the Rehabilitative Climate of a Re-Rolled Sexual Offender Prison: A Qualitative Longitudinal Study. (September 2020) - Blagden, Nicholas; Wilson, Kirsten
Understanding how individuals with sexual convictions experience prison and its environment is important because such experiences can affect rehabilitation outcomes. This is the first qualitative longitudinal investigation that explores the experiences of prisoners in a prison exclusively for individuals with sexual convictions over time. The purpose of this research was to explore the rehabilitative and therapeutic climate of a recently re-rolled prison (a general prison turned into a prison only for individuals who have sexually offended) at two time points (T1 at re-roll and T2 a year later). The study focuses on prisoners' perspectives of the purpose of the prison, experience of prison life, relationships in the prison, and the prison regime over time. Twenty interviews were conducted across the time points and revealed two main superordinate themes: "'Being' in a prison for individuals with sexual convictions" and "obstructions to change." This research adds to the emerging body of knowledge surrounding the importance of the wider prison environment on the rehabilitation of individuals with sexual convictions and on the benefits and risks of co-locating men who have committed sexual offenses in the same prison site. It also has implications wider than rehabilitation of those convicted of sexual offenses and has insights for the types of environment and prisoner–staff relationships that are conducive to rehabilitation.